The genus Paradorylaimus Andrássy, 1969 (Nematoda: Dorylaimida) with description of three new species from Ecuador - Orselli, Lara; Clausi, Mirella; Vinciguerra, Maria Teresa (Zootaxa, 2012)
Three new species of Paradorylaimus Andrássy, 1969, found in moss and litter of natural environments of Ecuador aredescribed. P. andinus sp. n. is characterized by 1.65–2.26 mm long female body, lip region set off by a depression, odontostyle26.5–32. 5 μm long and 3.0–4.5 µm wide; pre-rectum 1.1–2.4 anal body diameters long in female and 1.2–2.3 in male; 0–3 pre-vulval and 0–5 postvulval papillae; spicules 60–80 µm long; 13–14 ventral supplements; female tail elongate-filiform, 6–10anal body diameters long; male tail short, 0.7–1 cloacal body diameters long, dorsally convex, with a marked ventral concavityand blunt terminus. P. longicaudatus sp. n. is characterized by 1.78–2.14 mm long female body, lip region slightly set off by adepression, odontostyle 30–32.5 μm long and 2.0–3.5 µm wide; pre-rectum 1.3–2.3 anal body diameters long in female and 2–3.5 in male; paravulval papillae absent; spicules 44.5–62.5 µm long; 11–13 ventral supplements; female tail elongate-filiform,11–16 anal body diameters long; male tail short, 0.8–0.9 cloacal body diameters long, convex conoid, with blunt terminus. P.flagellicaudatus sp. n. is characterized by 1.65–1.73 mm long female body, lip region continuous, odontostyle 19–24 μm longand 2–2.5 µm wide; pre-rectum 1.8–2.6 anal body diameters long in female and 2.4 in male; spicules 45 µm long; 10 ventralsupplements; female tail elongate-filiform, 25–26 anal body diameters long; male tail short, conoid, 0.8 cloacal body diameterslong. The authors support the validity of the genus Paradorylaimus, provide an updated diagnosis and furnish a compendium of the main morphometric parameters of its species and a key to them.